Comparative investigation of seed coats of brown‐ versus yellow‐colored soybean seeds using an integrated proteomics and metabolomics approach. Issue 10 (10th February 2015) - Gupta, Ravi; Min, Chul Woo; Kim, So Wun; Wang, Yiming; Agrawal, Ganesh Kumar; Rakwal, Randeep; Kim, Sang Gon; Lee, Byong Won; Ko, Jong Min; Baek, In Yeol; Bae, Dong Won; Kim, Sun Tae; et al.
<x xml:space="preserve">Abstract</x> Seed coat color is an important attribute determining consumption of soybean seeds. Soybean cultivar Mallikong (M) has yellow seed coat while its naturally mutated cultivar Mallikong mutant (MM), has brown colored seed coat. We used integrated proteomics and metabolomics approach to investigate the differences between seed coats of M and MM during different stages of seed development (4, 5, and 6 weeks after flowering). 2DE profiling of total seed coat proteins from three stages showed 178 differentially expressed spots between M and MM of which 172 were identified by MALDI‐TOF/TOF. Of these, 62 were upregulated and 105 were downregulated in MM compared with M, while five spots were detected only in MM. Proteins involved in primary metabolism showed downregulation in MM suggesting energy in MM might be utilized for proanthocyanidin biosynthesis via secondary metabolic pathways that leads to the development of brown seed coat color. Besides, downregulation of two isoforms of isoflavone reductase indicated reduced isoflavones in seed coat of MM that was confirmed by quantitative estimation of total and individual isoflavones using HPLC. We propose that low isoflavones level in MM may offer a high substrate for proanthocyanidin production that results in the development of brown seed coat in MM.